The importance of halal consumption in forming a civilized Muslim - Muflih, Betania (2015)

(untitled)
This work investigates the methods and ideas of Imam Nursi regarding human civilization and to understand his lively scriptural approach to the importance of sticking to Allah’s guidelines. This article follows library and textual analysis. Hence, it concludes that it is necessary to situate Imam Nursi’s work within the context of Tauhid (Divine Unity) framework, which constitutes the background of his entire system of thought. The purpose of a Muslim's life is to worship Allah and to devote oneself to seeking His love. Imam Nursi argues that man is given faculties to discover Allah’s attributes that are manifested in the universe in different kinds of forms. Thus the humanity’s highest aim and purpose is to complete their faith with knowledge and love of Allah. So worshipping Allah takes many different forms too. This paper will highlight the idea of Consuming Halal food as one way of worshipping Allah and Devoting oneself to Him, and that Consuming Non-Halal food will lead oneself to commit wrongdoing. Imam Nursi’s ideas explain that Muslims need to adhere with fundamentals of faith in order to be civilized. Keywords: Civilization, Divine Unity, Halal Consumption